Production of La0.6Sr0.4Co0.2Fe0.8O3-δ cathode with graded porosity for improving proton-conducting solid oxide fuel cells. Issue 17 (1st December 2019) - Lai, Yi-Wei; Lee, Kan-Rong; Yang, Seng-Yu; Tseng, Chung-Jen; Jang, Shian-Ching; Tsao, I-You; Chen, Szu-yuan; Lee, Sheng-Wei
Abstract: Utilization of 500-nm-diameter polystyrene (PS) nanospheres as pore former in a screen printing process to tailor the porous structure of La0.6 Sr0.4 Co0.2 Fe0.8 O3-δ (LSCF) cathode for improving the performance of protonic solid oxide fuel cells is reported. The effects of PS nanosphere amount on cathode microstructure and cell performance are investigated. It is found that PS nanospheres can undergo a self-organized distribution in the screen-printed LSCF cathode due to the large difference in density between PS and LSCF, resulting in a porosity gradient in the cathode structure. The fuel cell with a 15 wt% PS-tailored cathode exhibits a much higher power density compared to that without tailoring by PS. The enhanced cell performance can be ascribed to the graded porosity in the cathode structure, which significantly reduces the ohmic and polarization resistances. It seems that such a graded-porosity cathode structure not only facilitates the generation and migration of O − ad from catalytic sites to triple phase boundaries (TPBs) but also promotes transfer of protons from the electrolyte to the TPBs.